HAKIKAT DAN FUNGSI PERATURAN PERUNDANG-UNDANGAN SEBAGAI BATU UJI KRITIS TERHADAP GAGASAN PEMBENTUKAN PERDA YANG BAIK - Jalaluddin, Jalaluddin (AKTUALITA, 2011)
In the concept of legal state (formal or material), the legislation such aslocal regulations has value that organize how people should behave. Thatrule should be appropriate with the fact and fuction of the legal ruleswhich organize their live as the reflection of the people will andaccordance with the requirements of justice and legal certainty. In thatposition, the fact and function of the legal rule will always be critical test -justification in making some good legislation. An academic text for theplan of legislation become the instrument to ensure that the legislation thatformed is accordance with the people wish as the fact and function of legalrules.Keywords: fact and function of Legislation, critical test-justification,academic text, the plan of the legislation-the good legislation.